Speech Enhancement using a Pitch Predictive Model - Droppo, Jasha; Acero, Alex; Yu, Dong; Deng, Li; Seltzer, Mike; Tashev, Ivan (Proceedings of the International Conference on Acoustics, Speech, and Signal Processing, 2008)
In this paper we present two new methods for speech enhancement based on the previously publised fine pitch model (FPM) for voiced speech. The first method (FPM-NE) uses the FPM to produce a nonstationary noise estimate that can be used in any standard speech enhancement system. In this method, the FPM is used indirectly to perform speech enhancement. The second method we describe (FPM-SE) uses the FPM directly to perform speech enhancement. We present a study of the behavior of the two models on the standard Aurora 2 task, and demonstrate improvements of over 45% average word error rate reduction over the multi-style baseline.